THE INFLUENCE OF CHILD GROWTH STATUS AND FAMILY RELATIONSHIPS ON THE SOCIAL-EMOTIONAL DEVELOPMENT OF PRESCHOOL-AGE CHILDREN - Widianingtyas, Sisilia Indriasari; Lusiani, Etik; Saputra, Agung Kurniawan (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: Social-emotional development is one of the most influential aspects of a child's subsequent development. Negative early experiences can lead to disruptions in children's mental health and affect their cognitive, behavioral, and social-emotional development. Children who can adjust socially and emotionally well will perform better at school, have increased self-confidence, have good relationships, take on and persist in challenging tasks, and communicate well. Objectives: The purpose of this study was to determine the effect of growth and family relationships on the social-emotional development of preschool-age children. Methods: The design of this study is observational research (non-experimental) with a cross-sectional research design, to see the relationship between the influence of child growth, and family relationships with social-emotional development. The instrument used in this study was a questionnaire. The statistical test used in this study is coefficient regression with a significance level of p 0.05. Results: The results showed that the level of social-emotional development in preschool children in kindergarten. ADNI Surabaya 72% (47) medium category. Child growth variables have a significant positive effect on children's socio-emotional development, and mother-child attachment has a significant positive impact on children's socio-emotional development. Conclusion: It is recommended that the Principal of ADNI Kindergarten strive for continuous education on good parenting patterns, attachment between mothers and children, how to improve children's ability to socialize, and how to stimulate children's growth and development, to achieve optimal children's socio-emotional development.